Harmonisasi Regulasi Pemilu dalam Konteks Pemilu Serentak 2024 - Moh Arief Erawan; Marten Bunga (Lembaga Pengembangan Kinerja Dosen, 2025)
The 2024 simultaneous elections in Indonesia are a major challenge in harmonizing regulations covering legislative and executive elections. The background of this research is the existence of overlapping regulations, norm gaps, and technical obstacles in implementation, which have the potential to affect the quality of democracy. This study aims to analyze the effectiveness of harmonization of electoral regulations, identify obstacles in implementation, and provide recommendations for improvement. The type of research used is normative juridical with statutory and conceptual approaches. The results show that regulatory harmonization can be achieved through synchronization between Law No. 7/2017 and implementing regulations, optimizing the role of EMBs, and applying digital technology for transparency and efficiency. The conclusion of this study is that regulatory harmonization is not only important to ensure fairness and equality in the electoral process, but also to increase public confidence in the integrity of elections in Indonesia. The findings are expected to serve as a reference for policymakers in facing the challenges of the 2024 simultaneous elections.